Depression symptoms, communication and cooperation skills, and friendship: longitudinal associations in young Norwegian children - Krygsman, Amanda; Vaillancourt, Tracy; Janson, Harald; Idsoe, Thormod; Nærde, Ane (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction: Depression symptoms in early childhood have been linked to interpersonal difficulties, whereas friendships serve a protective function.Methods: In the present study, we examined depression symptoms in preschool age (4 years) in relation to social skills (communication and cooperation), and friendships into early school age (Grades 1 and 2) in a large subsample (n=943) of Norwegian children. Results: Results indicated that preschool depression symptoms negatively predicted Grade 1 communication skills, which in turn predicted Grade 2 depression symptoms. This pathway suggests that communication skills may be a maintenance factor for depression symptoms in young children. Also, preschool depression symptoms predicted lower Grade 1 cooperation skills, which in turn predicted lower Grade 2 communication skills, suggesting that preschool depression symptoms may begin a cascade of social skill problems that affects cooperation and communication skills into early school years. Best friendships were negatively related to depression symptoms in preschool and Grade 2.Discussion: Given that preschool depression symptoms impact the development of social skills and friendships, it is important to attend to depression symptoms in early childhood.